Pyromellitic acid-sarcosine (1/2) - Domingos, S. R. (2008)
The title compound, C(10)H(6)O(8)·2C(3)H(7)NO(2), crystallizes as an adduct with the acid and amino acid mol-ecules in their neutral forms. The asymmetric unit contains one half of a centrosymmetric pyromellitic acid mol-ecule and one sarcosine mol-ecule. The sarcosine has the amine group protonated and the carboxyl group deprotonated, as is usual for amino acids (zwitterionic form). The pyromellitic acid mol-ecules retain the four carboxyl H atoms with the carboxyl groups rotated out of the ring plane [O-C-C-C torsion angles = 24.1 (3) and 61.6 (2)°]. There is a three-dimensional hydrogen-bond network linking the mol-ecules.